The Development of Kuttab Institutions within the Cultural Dominance of Traditional Pesantren (Islamic Boarding Schools) - Nursapaah, Nolis (Indonesian Journal of Research in Islamic Studies, 2026)
Background: Islamic education in East Java has long been dominated by traditional pesantren affiliated with Nahdlatul Ulama (NU), which has formed a strong socio-religious and cultural foundation. In recent years, however, the re-emergence of Kuttab as a classical Islamic educational model has introduced a new dynamic within this established landscape. Objective: This study aims to analyse the development of Kuttab institutions in East Java, examining their characteristics, challenges, and adaptation strategies within the dominant pesantren culture. The research employs a qualitative approach with a descriptive case study design. Data were collected through in-depth interviews, document analysis, and review of relevant scholarly literature. Result: The findings indicate that Kuttab has gained positive acceptance among parents seeking Qur’anic and character-based education for early-age children. Nevertheless, the institutions face challenges related to legal recognition, curriculum standardisation, teacher professionalism, infrastructure, and socio-cultural perception.  Conclusion: The study concludes that sustainable development of Kuttab requires regulatory reinforcement, contextual curriculum development, professional capacity building, and institutional collaboration. Contribution: This study contributes to the discourse on contemporary Islamic education by providing contextual insights into the interaction between revitalised classical models and entrenched traditional educational systems in Indonesia.